VOLUMELY PLANNABLE SOLUTIONS AND DESIGN OF PREMISES OF EQUESTRIAN SPORTS COMPLEX IN MODERN CONDITIONS - Zhydkova, Tetiana; Matyushchenko, Nataliia; Kichnyaeva, Olena (Theory and practice of design, 2024)
The problem of creating a comfortable and safe environment for keeping horses in equestrian sports complexes, at stud farms in the conditions of modern war is covered in the article. The main requirements of regulatory documentation, the results of research by specialists in the field of animal husbandry, providing daylight in houses with the help of modern technologies, and the peculiarities of the perception of environmental colors by animals have been analyzed. The purpose of this is the development of proposals for the volume-planning solution of the stable building and the design of the premises for a comfortable and safe stay of horses in the equestrian complex in modern conditions. The main tasks of the research: to analyze the current state and volume-planning structure of buildings for keeping horses; to analyze the peculiarities of perception of the external environment by horses; to develop a scheme of the volume-planning structure of the stable, which will ensure the preservation of the life and health of animals. Methodology. Theoretical research methods, analysis of current regulatory documentation, articles in specialized publications, experience of countries around the world and the war in Ukraine were used. The results. Spatial planning solutions and design of stable premises for creating an energy-efficient, comfortable and safe environment for keeping horses in equestrian sports complexes, stud farms, and racetracks are proposed. An evacuation scheme for animals and personnel has been developed. Safe areas in the stable, where animals can stay for a short time during air raids and missile attacks, as well as in winter when the outside temperature drops, are defined. A solution for providing daylight in the stables in accordance with the needs of the horses is proposed. Practical significance. Research results can be used in practice to create a comfortable and safe environment for keeping horses in equestrian sports complexes, stud farms, racetracks, etc.